Stress dose explains drought recovery in Norway spruce - Knüver, Timo; Bär, Andreas; Hamann, Elias; Zuber, Marcus; Mayr, Stefan; Beikircher, Barbara; Ruehr, Nadine K. (Frontiers in Plant Science, 2025)
IntroductionUnderstanding the stress recovery of trees, particularly with respect to increasing droughts due to climate change, is crucial. An often-overlooked aspect is how short versus long drought events of high intensity (i.e., low and high stress dose) result in stress damage and affect post-stress recovery.MethodsThis study examines the stress and recovery dynamics of 3-year-old Picea abies following a short drought (n = 5) of 18 days or a long drought (n = 9) of 51 days during late summer. We particularly assessed how the recovery of canopy conductance and tree transpiration is linked to i) stress intensity in terms of minimum water potential, ii) stress duration inferred by days below a water potential related to 12% hydraulic conductance loss (dP12), iii) stress dose inferred by the cumulative tree water deficit on days below P12 (TWDP12) as well as the cumulative water potential (Ψcum), and iv) the percent loss of conductive xylem area (PLA).ResultsBoth drought treatments resulted in stem and root embolism with a higher PLA of 49% ± 10% in the long drought treatment compared to 18% ± 6% in the short drought treatment consistent across the measured plant parts. Suffering from embolism and leaf shedding (long drought, 32%; short drought, 12%), canopy conductance in the long drought treatment recovered to 41% ± 3% of the control and in the short drought treatment to 66% ± 4% at 12 days after drought release. These recovery rates were well explained by the observed PLA (R2 = 0.66) and the dP12 (R2 = 0.62) but best explained by stress dose metrics, particularly the cumulative TWDP12 (R2 = 0.88).DiscussionOur study highlights that stress duration and intensity should be integrated to assess post-stress recovery rates. Here, the tree water deficit derived from point dendrometers appears promising, as it provides a non-destructive and high temporal resolution of the stress dose.